Does task delegation to non-physician health professionals improve quality of diabetes care? Results of a scoping review. - Sanas Mirhoseiny; Tjarko Geelvink; Stephan Martin; Horst Christian Vollmar; Stephanie Stock; Marcus Redaelli (PLoS ONE)
Objective As a result of unhealthy lifestyles, reduced numbers of healthcare providers are having to deal with an increasing number of diabetes patients. In light of this shortage of physicians and nursing staff, new concepts of care are needed. The aim of this scoping review is to review the literature and examine the effects of task delegation to non-physician health professionals, with a further emphasis on inter-professional care. Research design and methods Systematic searches were performed using the PubMed, Embase and Google Scholar databases to retrieve papers published between January 1994 and December 2017. Randomised/non-randomised controlled trials and studies with a before/after design that described the delegation of tasks from physicians to non-physicians in diabetes care were included in the search. This review is a subgroup analysis that further assesses all the studies conducted using a team-based approach. Results A total of 45 studies with 12,092 patients met the inclusion criteria. Most of the interventions were performed in an outpatient setting with type-2 diabetes mellitus patients. The non-physician healthcare professionals involved in the team were nurses, pharmacists, community health workers and dietitians. Most studies showed significant improvements in glycaemic control and high patient satisfaction, while there were no indications that the task delegation affected quality of life scores. Conclusions The findings of the review suggest that task delegation can provide equivalent glycaemic control and potentially lead to an improvement in the quality of care. However, this review revealed a lack of clinical endpoints, as well as an inconsistency between the biochemical outcome parameters and the patient-centred outcome parameters. Given the vast differences between the individual healthcare systems used around the world, further high-quality research with an emphasis on long-term outcome effects and the expertise of non-physicians is needed.